Exploring the effects of Tianma Gouteng granules on L-NAME-induced hypertensive rats based on 16S rDNA gene sequencing and metabolomics - Li Cheng; Zhenyang Huang; Jiawei He; Xinyi Zhang; Jiangxue Di; Hanmei Jiang; Yi Liu (Heliyon)
Background: A growing number of studies have shown that hypertension symptoms are closely related to intestinal flora. The body's metabolites are closely related to disease states. Tianma Gouteng Granules (TG), a traditional Chinese medicine compound, has been proven to be an effective compound for the treatment of hypertension by traditional Chinese medicine diagnosis, but the target and therapeutic mechanism of TG on hypertension are still unclear. Aim of the study: We explored the mechanism of action of TG on hypertension by 16S rDNA gene sequencing and non-targeted metabolomics, verified the correlation between hypertension and intestinal flora, searched for potential markers of intestinal flora, and screened for the correlation between different flora and different metabolites, which facilitates a more scientific and reasonable guidance for the administration of TG. Materials and methods: The hypertensive model rats were induced by L-NAME. After drug administration, 16S rDNA gene sequencing and non-targeted metabolomics were applied to detect and analyze the intestinal flora and fecal metabolites of the rats in each group. The Spearman coefficient method was used to construct the interactions system of different flora and metabolites, which explore the potential mechanism of TG treatment hypertension. Results: After TG administration, the symptoms of hypertension were significantly reduced to normal in SD rats.16S rDNA gene sequencing and non-targeted metabolomics screened for differential flora p_Actinobacteriota, o_Micrococcaceae, f_ Micrococcales, g_Rothias_Rothia_unclassified, etc. and differential metabolites such as L-Alanine and Hydroxyprolyl-Leucine. TG treatment of hypertension was found to be associated with vitamin B6 metabolic pathway and lipid metabolic pathway. Conclusions: TG can treat hypertension by affecting differential strains and differential metabolites, providing a scientific basis for guiding the rational use of TG.